Penatalaksanaan Holistik Pada Pasien Tuberkulosis Melalui Pendekatan Kedokteran Keluarga - Putri Octavia Sari; Tutik Ernawati (Majority, 2020)
Indonesia ranks third in most cases of tuberculosis (TB) in the world. This is due to the low knowledge about TB and the low level of medication taking. Therefore, the role of family doctor is needed to manage patients holistically from various aspects. This study is a descriptive study of case reports. Primary data were obtained through alloanamnesis, physical examination and home visits. Secondary data were obtained from the patient's medical record. Patient Mr. A, 21 years old, came for routine TB treatment and has been diagnosed two months ago. The patient has poor nutritional status. Problems needed by patients are lack of physical activity, lack of patient knowledge of TB, lack of family support and smoking habits. Regarding pharmacological and non-pharmacological intervention in patients is education about the disease for patients and families. The evaluation results of the intervention are that patients who have begun physical and family activities have supported for routine treatment. But patient’s family still have the habit of smoking indoors. Holistic management of TB patients is needed. The patient's level of knowledge about the disease and the importance of the family knowing the schedule for treatment and a healthy lifestyle determine the success of TB treatment. Patient and Family took doctor’s advice well after intervention, but lifestyle changes such as smoking habit haven’t done optimally